Tư duy hệ thống trong công việc =The art of thinking in systems / Steven Schuster; Diệp Ngô - Schuster, Steven
Tên sách tiếng Anh: The art of thinking in systems: improve your logic, think more critically, and use proven systems to solve your problems - strategic planning for everyday life